Establishment of a rapid methodology for quantitative monitoring of monoclonal antibodies production - Premazzi, Melissa Chamon Alves (2025)
Fundação Oswaldo Cruz. Instituto de Tecnologia de Imunobiológicos. Rio de Janeiro, RJ, Brasil.